Screen exposure, sleep quality, and language development in 6-month-old infants - Sanchez-Bravo, Dayanara; Sandre, Aislinn; Amarante, Melina; Wiltshire, Cynthia A.; Noble, Kimberly G. (Frontiers in Developmental Psychology, 2025)
IntroductionScreen time can have important ramifications for children's development and health. Children exposed to greater screen time score lower on assessments of language development and tend to sleep less. However, most studies examining associations among screen time, language development, and sleep quality have focused on older children and/or have relied on subjective assessments of screen time exposure (i.e., parent report). The current study examined whether screen exposure, assessed via both maternal-report questionnaires and in-home audio recordings, was associated with differences in language development and sleep quality in infants at ~6 months of age (N = 187).MethodsMothers completed questionnaires to assess infant screen exposure, language production, and sleep quality, as well as family socioeconomic and demographic factors. The Language Environment Analysis (LENA) recorder was used to measure home screen use and the language environment.ResultsHigher family income and higher maternal education were associated with less infant screen time, as assessed by both maternal report and in-home LENA recordings. Neither measure of infant screen exposure was significantly associated with the home language environment, maternally-reported infant language production, or infant sleep quality. Maternally-reported screen exposure showed a small but significant positive correlation with LENA-derived screen exposure.DiscussionWe find no detectable association between screen exposure and differences in maternally reported language development or sleep quality in the first 6 months of life. Future studies will be needed to examine associations among screen time and subsequent infant development and health outcomes.